Comparison of D-dimer level measured on the third day of hospitalization with D-dimer level in predicting in-hospital mortality in COVID-19 patients. (14th October 2021) - Selcuk, M; Cinar, T; Gunay, N; Keskin, M; Cicek, V; Kilic, S; Asal, S; Orhan, A L
Abstract: Objective: The present study aimed to compare the value of D-dimer measured on the 3rd day of hospitalization with admission D-dimer level in predicting in-hospital mortality in coronavirus disease 2019 (COVID-19) cases. Method: In total, 231 patients with COVID-19 disease were included in the study. D-dimer levels were estimated using immunoturbidimetric assay with normal range of 0–500 μg/mL. In the current research, the primary outcome was the in-hospital mortality. Results: In the present research, 39 (16.8%) COVID-19 cases died during the index hospitalization. In a multivariable analysis; age, D-dimer (3rd day) (OR: 1.00, 95% CI: 1.00–1.00, p<0.001), WBC count, and creatinine were independent predictors of the in-hospital death for COVID-19 cases. The ideal value of D-dimer level on the 3rd day of hospitalization was 774 μq/mL (area under curve (AUC): 0.903, 95% CI: 0.836–0.968; p<0.01) with sensitivity of 83.2% and specificity of 83.6%. It was noted that D-dimer level on the 3rd day of hospitalization had a higher sensitivity (83.2% vs 67.6%, respectively) and AUC value than that of D-dimer level on admission (0.903 vs 0.799, respectively). Conclusion: The main finding in this investigation was that D-dimer elevation on the 3rd of hospitalization is more sensitive predictor of in-hospital mortality than D-dimer elevation on admission in COVID-19 patients. Even though further investigations are needed to forecast precise prognosis in patients with COVID-19 disease in terms of D-dimer levels, we believe that D-dimer levels on the 3rd day of hospitalization have an enhanced potential to be used as a prognostic marker in routine clinical practice. FUNDunding Acknowledgement: Type of funding sources: None.